Isoscutellarein from Bixa orellana Leaves Uncompetitively Inhibits Recombinant Human Aldose Reductase and Prevents Sorbitol Accumulation and Lens Opacity - Durgam, Mohan K.; Bodiga, Vijaya Lakshmi; Vemuri, Praveen Kumar; Bodiga, Sreedhar (Current Enzyme Inhibition, 2023)
Background: Enhanced aldose reductase activity results in increased accumulation of sorbitol. Therefore, inhibition of aldose reductase is an effective strategy to prevent or delay certain diabetic complications. Methods: Various extracts of the leaves of B. orellanawere tested for their inhibitory activity on the aldose reductase. Ethyl acetate extract that showed maximum inhibition was further fractionated and the inhibitor was identified as isoscutellarein by spectroscopic methods. IC50 of recombinant human aldose reductase by isoscutellarein was found to be 14 μM and the mode of inhibition was uncompetitive with a decrease in both Km and Vmax. Isoscutellarein was bound to the active site of aldose reductase (3RX3), namely to Ala-299, Leu-300, Leu-301, His-110 and Tyr-48. Results: Docking results exhibited a binding energy of -9.15 kJ/mol. Conclusion: The incubation of red blood cells with high glucose concentrations mimicking hyperglycemic conditions promoted sorbitol accumulation, which was effectively inhibited by isoscutellarein. Further, xylose-induced opacity of the lens was effectively inhibited by isoscutellarein.
Keywords: polyol pathway